Liability for Crypto Asset Transactions Ethereum in Indonesia - Mahesa Dharma Adji; Hervina Puspitosari (Fakultas Hukum Universitas Widya Mataram, 2023)
Ethereum is a decentralized digital currency andplatform blockchain which has gained popularity in Indonesia. Crypto assets have inherent risks, such as price volatility and the potential for fraud or hacking which is of course very detrimental to their users. Based on this, it is necessary to explore the accountability of parties using crypto assetsEthereum as an object of trade. The type of research used is normative juridical with an approach taken to statutory regulations. The results of the research show that liability can occur for default, unlawful acts, and unlawful acts. The form of liability that can be taken is in the form of cancellation of the agreement to claims for compensation by the aggrieved party. The government, in this case, needs to buy educational outreach to the public on the wise use of crypto assets.